Dìêslìvnì sininìmì v hudožnìh tvorah I. Nečuâ-Levic’kogo - Mâlkovs’ka, Lûdmila (Stylistyka, 2019)
The author of the paper analyzes verbs ‘talk’ and ‘think’ found in texts by I. NechujLevitsky. Many of those verbs and their synonyms together with their metaphorical and phraseological uses are applied to reconstruct their semantic fields. The language means used to illustrate and describe the processes of talking and thinking analyzed in the paper make it possible to conclude that the frequent occurrence of those verbs in his texts is a characteristic feature of Nechuj-Levitsky’s personal style.